2020
DOI: 10.1111/cpr.12867
|View full text |Cite
|
Sign up to set email alerts
|

Effects of propofol on the development of cancer in humans

Abstract: Cancer is one of most the significant threats to human health worldwide, and the primary method of treating solid tumours is surgery. Propofol, one of the most widely used intravenous anaesthetics in surgery, was found to be involved in many cancer‐related pathophysiology processes, mainly including anti‐tumour and minor cancer‐promoting effects in various types of cancer. An increasing number of studies have identified that propofol plays a role in cancer by regulating the expression of multiple signalling pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 82 publications
0
52
0
Order By: Relevance
“…Propofol is a short‐acting intravenous anesthetic commonly used in surgery and is related to the pathophysiological process of many diseases 5,6 . Existing studies have identified that propofol plays an anticancer role in various cancers by regulating non‐coding RNAs and multiple signaling pathways 7 . Nevertheless, the underlying mechanism of propofol‐induced antitumor activity remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Propofol is a short‐acting intravenous anesthetic commonly used in surgery and is related to the pathophysiological process of many diseases 5,6 . Existing studies have identified that propofol plays an anticancer role in various cancers by regulating non‐coding RNAs and multiple signaling pathways 7 . Nevertheless, the underlying mechanism of propofol‐induced antitumor activity remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to anesthesia, propofol also affects immunity, inflammation, and ischemia reperfusion injury 4 , 19 . Propofol has been reported to induce antitumor immunity by promoting T-assisted cell activation and differentiation 20 22 and can inhibit the viability, migration, and invasion of bladder cancer T24 cells in vitro 23 . In this study, we explored the effects of propofol on the proliferation, migration, and stem-like properties in three bladder cancer cell lines, identified its underlying mechanisms, and further validated its effects in primary human bladder cancer cells and mice xenografts in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…One of the interesting points is the anti-tumor activity of propofol as an anesthetic agent. This compound is exclusively applied in cancer therapy, and it is capable of regulating different molecular pathways in cancer therapy, particularly miRNAs [ 320 , 321 , 322 ]. In non-small cell lung cancer, propofol downregulates miRNA-21 expression to induce apoptosis in a time- and dose-dependent manner.…”
Section: Microrna and Pten Relationshipmentioning
confidence: 99%